Improved delayed detached eddy simulations applied to a NACA0015 aerofoil subject to acoustic excitation - Coskun, Seyfettin; Pachidis, Vassilios; Ubulom, Iroizan; Bacic, Marko (AIAA, 2022)
The effect of acoustic excitation on the aerodynamic performance of NACA0015 aerofoil at $\alpha=11^{\circ}$ and $Re_c = 1.0 \ x 10^6$ based on $c=0.35m$ chord length is investigated numerically using Improved Delayed Detached Eddy Simulations (IDDES). Flow separation is observed over the suction surface in the uncontrolled flow that forms a separated shear layer, resulting in aerodynamic performance degradation. External acoustic excitation is used in controlling the flow separation by exciting the separated shear layer. Acoustic excitation frequency and amplitude are the control parameters considered. The flow field is excited at a frequency of the most amplified disturbances and at first harmonic and sub-harmonic frequencies with a constant excitation amplitude. Unlike the harmonics, when the separated shear layer is excited at $F+=1$, the separation characteristics of the uncontrolled flow field are significantly altered. Unsteady disturbances are locked into the excitation frequency and transition is promoted within the shear layer. A separation bubble is generated over the suction surface with a reattachment region aft of the aerofoil surface. Vortex coherence and organized wake structures are also improved. The effect of excitation amplitude is investigated at the frequency of the most amplified disturbances. Increasing the excitation amplitude has two predominant impacts; it delays the boundary layer separation and advances the reattachment location, thereby reducing the separation bubble length. The results also suggest that there is a maximum effective acoustic excitation amplitude.